Analysis of HIRARC Implementation and Understanding of HIRARC on Work Accidents through Work Environment - Nugroho, Agung (SAFE-Network, 2025)
The study was conducted with the aim of analyzing the effect of HIRARC implementation and understanding of HIRARC both directly and through the work environment on work accidents. The research was conducted at PT ABC located in Nabire Regency. The research was conducted with a quantitative approach and included causal associative research. The sample in this study were 250 production employees of PT ABC and data collection was carried out using a questionnaire. The data analysis technique was carried out using path analysis. The results showed that the implementation and understanding of HIRARC directly have a significant effect on work accidents. Other results show that the implementation and understanding of HIRARC through the work environment have a significant effect on work accidents in production employees of PT ABC. The study implies that management must strengthen its commitment to integrating HIRARC into operations, provide ongoing practical training, and regularly evaluate OHS performance based on HIRARC effectiveness and work environment quality to support continuous improvement and reduce work accidents.